VD_FINDINFO HC / 2013 / 32 vom 7. Januar 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, CONCLUSION DU CONTRAT, PREUVE, FORCE PROBANTE, CONSTATATION DES FAITS | 8 CC, 11 CO, 253 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 308 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)